Introduction Of EVA (Economic Value Added) As A Management Performance Evaluation System In Malaysia - Ming, Siew Fook (2005)
The objective of this thesis is to find a proper management performance evaluation measure that is fitting for sustainable wealth creation for shareholders and right decision making for Malaysian companies. To enhance effective implementation , simulation programmes are developed using EVA concepts.